Di-Higgs signatures in neutral naturalness - Barela, Mario W. [UNESP]; Capdevilla, Rodolfo (My University, 2024)
The Higgs boson was the last fundamental piece of the Standard Model to be experimentally confirmed. LHC is embarked in a quest to probe the possibility that this particle provides a portal to new physics. One front of this quest consists in measuring the interactions of the Higgs with itself and with other SM particles to a high precision. In a more exotic front, the LHC is searching for the possibility that a pair of Higgses (HH) is the evidence of a new resonance. Such resonances are predicted in models with extended Higgs sectors, extra dimensions, and in models with exotic bound states. In this paper we show how scalar quirks in Folded Supersymmetry can give rise to HH resonances. We point out a viable sector of the parameter space in which HH is the dominant decay channel for these squirkonium bound states. We found that future runs of the LHC could discover HH resonances in the range of 0.5–1.6 TeV under reasonable assumptions. Furthermore, for a given mass and width of the HH signal, the model predicts the branching ratio of the subsequent decay modes of the heavy resonance. Finding the extra decay modes in the predicted pattern can serve as a smoking gun to confirm the model.
Keywords: Hierarchy Problem; Other Weak Scale BSM Models